Grammatical Relations of German and Indonesian language in Criminal Texts Der Spiegel and Kompas - Siahaan, Sahat Taruli; Mulyadi, Mulyadi (Journal of Language Development and Linguistics, 2024)
This study aims to analyze the types of grammatical relations that appear in Germany in the German criminal text Der Spiegel and Indonesian in the Indonesian criminal text Kompas. The data in this study are 127 clauses in German and 90 clauses in Indonesia. The data sources in this study are 3 German crime texts in the German (online) magazine Der Spiegel and 3 Indonesia newspapers Kompas  in the May 2024 issue. The research design used is Qualitative Descriptive. Data collection was carried out using critical reading and note-taking techniques. Meanwhile, the approach used in this study is the Typology approach of Comrie (1981) and Farrel (2005). The results of this study show that there are: (1) 4 types of grammatical relations, namely Nominative with 13 findings (10%), Nominative-Acoussative with 48 findings (38%), Active language with 44 findings (35%) and Passive language with 22 findings (17%) appear as types of grammatical relations that occur in German in  the online criminal text Der Spiegel; (2) 4 types of grammatical relations found in Indonesian criminal texts in Kompas, that is Nominative with 7 findings (8%), Nominative-Accusative with 38 findings (42%), Active language with 32 findings (36%) and Passive language with 13 findings (14%); (3) the Nominative-Accusative grammatical relationship type with 48 findings (38%) is the dominant one found in the German criminal text in  the May 2024 edition of Der Spiegel online; and (4) the Nominative-Accusative grammatical relationship type with 38 findings (42%) is the most dominant in the Indonesian crime text in the May 2024 issue of the Kompas newspaper.